Studi Etika Pelajar Terhadap Guru Dalam Pendidikan Islam Perspektif KH. Hasim Asy'ari - Husnul Mu'amalah (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2019)
Indonesia is facing a serious threat regarding the decline of the nation's morale, this can be seen from the low ethical values related to the low morale of the nation related to the low morale of students, such as the case of student abuse against teachers, this is due to the lack of knowledge of students in knowing the ethics they should have in studying. For this reason, students need to gain ethical knowledge, either by learning from the teacher or by studying books, books and studies that discuss ethics. While the purpose of this study is to determine the ethics of students towards teachers in Islamic education from the perspective of KH. Hasyim Asyari in the adab al-alim wa almuta 'allim book. This research is a library research that uses a descriptive qualitative approach to collect data by collecting from books, books, magazines, internet, and then the data is analyzed and concluded.